SIMULATION OF SPATIAL KINEMATICS diplacement SYSTEM with INTERACTIVE vizualzition of results - S. E. Karpovich; V. V. Kuzniatsou; M. M. Forutan (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The mathematical model for calculation of position functions of controlled positioners depending on position and orientation of execution platform of motion system in three-dimension space with six degrees of freedom was developed. The model allows carrying out the imitational modelling of kinematic characteristics of spatial motion system with interactive visualization in MATLAB environment.